Novel amino-ethyl carboxymethyl cellulose crosslinked ampholyte hydrogel development for Methyl Orange Removal from Waste water: Kinetics, isotherms, and thermodynamics studies - Ahmed M. Omer; Wagih Abdel-Alim Sadik; Rafik Abbas Elady; Tamer M. Tamer; Mai Mohammed Abd-Ellatif; Mohamed S. Mohy-Eldin (Desalination and Water Treatment)
In this study, a novel ampholyte hydrogel known as amino-ethyl carboxymethyl cellulose crosslinked hydrogel (AECMC) was synthesized and utilized to remove Methyl orange (MO), an azo-dye commonly found in dyes contaminated wastewater. This marks the first instance of such a hydrogel being generated for this specific application. The presence of induced amine groups in the modified carboxymethyl cellulose matrix facilitated the creation of adsorption positive charge centers, which effectively attracted MO azo-dye anions. The level of amination exhibits a clear correlation with both the percentage of MO adsorption and the capabilities of adsorbents. An initial rapid adsorption phenomenon was seen within the first 15 min, followed by a gradual decrease in the rate of adsorption until reaching a plateau. The adsorption capacity is notably influenced by the temperature of adsorption, particularly in the case of employing low aminated carboxymethyl cellulose (CMC) derivative. The aforementioned effect exhibits a decrease in magnitude when increasing levels of aminated carboxymethyl cellulose (CMC) derivatives are employed. The kinetics of the adsorption process was assessed by the use of three models: Pseudo-first-order, Pseudo-second-order, and Elovich. Moreover, the mechanism of the adsorption process was monitored using two models, namely Dumwald–Wagner and intraparticle models, which described the liquid film diffusion or intraparticle diffusion, while the external mass transfer was examined by the Boyd model. The Boyd diffusion model determines that the process rate is limited by film diffusion. Additionally, the adsorption isotherm was examined using established models such as Langmuir, Freundlich, and Temkin isotherms. The thermodynamic characteristics of the MO adsorption process have been investigated at various adsorption temperatures using the Van't Hoff model. The results obtained from the study indicate that the process of MO adsorption adhered to the Pseudo-second-order kinetic model. Additionally, the Langmuir isotherm model was found to be applicable, with a maximum adsorption capacity of 2.033 mg/g for the Langmuir monolayer. Furthermore, it was observed that the adsorption process was spontaneous and exhibited an endothermic character.